Design and evaluation of a high-performance extensible DC-DC converter integrated with ANN based MPPT controller - Motakabber, S. M. A.; Akter, Khadiza; Alam, A. H. M. Zahirul; Yusoff, Siti Hajar (IEEE, 2023)
Boosting the low voltage output to achieve the required utility voltage is one of the main issues with solar photovoltaic sources. To effectively utilize solar energy at the highest power, point these systems frequently utilize high performance boost DC-DC converters as interfacing circuits to fulfill the load demand. A novel expandable non-isolated step up DC-DC converter with 94% transformation efficiency is reported here. Moreover, a comparison of converters in terms of efficiency, gain in output voltage, the potential stress on semiconductors, and operating principle among various topologies has been executed. The basic design of the suggested converter features a large voltage gain (more than 20) and lessened stress on the diode and Metal Oxide Semiconductor Field Effect Semiconductor (MOSFET) as compared to the typical existing topology. Artificial Neural Networks (ANN) based algorithm is used in the construction of Maximum Power Point Tracking (MPPT) controllers as they are thought to be a faster, more accurate, and more reliable estimating technique than other techniques. Utilizing MATLAB/SIMULINK, simulation results are performed to verify theoretical notions.